Skyping the Family. Interpersonal video communication and domestic life - Rod Watson (Benjamins Current Topics, 2019)
This collection is one of the first in-depth studies of video calling in family and domestic life. It explores the reasons that people themselves provide to explain their video calling, investigates how these reasons make that calling accountable and how, in turn, these reasons come to be things talked about in the calls themselves. The research shows how video calling is part of the currency of contemporary family affection: such calls are not just about keeping in touch, they are a way of loving too; and they are sometimes a way of fighting as well. 'Skyping' or 'Facetiming' might be frequent and can seem mundane - just a question of routine - but what they entail is a measure of important things to families. This makes this collection of interest to anyone concerned with family life and the evolving ways in which technology has a role in it.